Spatial and temporal imaging of long-range charge transport in perovskite thin films by ultrafast microscopy - Guo, Zhi (Nat Commun, 2015)
Charge carrier diffusion coefficient and length are important physical parameters for semiconducting materials. Long-range carrier diffusion in perovskite thin films has led to remarkable solar cell efficiencies; however, spatial and temporal mechanisms of charge transport remain unclear. Here we present a direct measurement of carrier transport in space and in time by mapping carrier density with simultaneous ultrafast time resolution and ∼50-nm spatial precision in perovskite thin films using transient absorption microscopy. These results directly visualize long-range carrier transport of ∼220 nm in 2 ns for solution-processed polycrystalline CH(3)NH(3)PbI(3) thin films. Variations of the carrier diffusion coefficient at the μm length scale have been observed with values ranging between 0.05 and 0.08 cm(2) s(−1). The spatially and temporally resolved measurements reported here underscore the importance of the local morphology and establish an important first step towards discerning the underlying transport properties of perovskite materials.